DAKWAH INTERAKTIF: TEORI INTERAKSI SIMBOLIK DALAM PENYEBARAN PESAN ISLAM ONLINE - Tarmizi, Rahasbi; Azizi, Muhammad Abrar (Program Studi Komunikasi dan Penyiaran Islam, 2023)
The development of information technology has transformed the paradigm of da'wah communication from one-way to more interactive. In this context, symbolic interaction theory offers a relevant analytical framework for understanding the dynamics of the dissemination of Islamic messages online. This article aims to examine digital da'wah practices through the lens of symbolic interaction, where symbols, meanings, and audience responses play a central role in shaping effective da'wah communication. Through literature review and qualitative approach, this paper highlights the importance of shared meaning, two-way interaction, and the role of religious symbols in reinforcing Islamic messages in the digital space. Interactive da'wah is not merely about conveying religious information but also about fostering dialogue and shared religious identity between da'is and digital congregations